Contribuciones al conocimiento sobre la ecología y distribución geográfica de phrynops (batrachemys) dahli; (testudinata, pleurodira, chelidae) (1966)
1. Data on Ecology, Behavior and Geographical Distribution of the chelid turtle, Phrynops (Batrachemys) dahli, are reported. 2. The original habitat of the "carranchina" or "cabeza al lado" consisted in ponds and small brooks within the forests, a situation which has gradually changed; actually the entire area around the type locality is transformed into pastures. 3. It is principally carnivorous and feeds on snails, aquatic insects, tadpoles, frogs, small fishes, carrion, but also sometimes on vegetable matter. No endoparasites had been found. 4. A marked dimorphism exists between the two sexes (figs. 2, 4, 5). 5. The mating season takes place in June-July approximately. 6. From one to six white, hard-shelled, slightly ellipsoid eggs are laid mainly in September-October; they measure between 35.5 : 29.0 mm. and. 28.0 : 23.5 mm. (fig. 7). 7. In several females, captured in May 22, 1958, which died in June 1959, hard-shelled eggs and numerous ovules had been found. 8. A female, captured in September 24, 1963, laid October 22, 1963, four eggs in a shallow groove without covering them, possibly due to lack of time or the hard soil full of pebbles. Three of those eggs were apparently not fertilized and became dry within two months; the last one was finally opened in August 14, 1964; it measured 34.5 : 26.5 mm. and contained a Fetus almost ready to hatch (fig. 6); its Carapax measured 28.0 mm, (length) and 22.5 mm. (width); the very protruding vitelline sack (12.0 : 11.0 mm.) still covered the Plastron; an easy discernible Oviruptor was present. This does not necessarily mean that the incubation period normally lasts over ten months, but rather seems to indicate that the eggs are resistant enough to develop in spite of a prolonged dry season - common in the given area - without suffering lethal effects. 9. Taken from the great number of ovules in different state of development, together with hard-shelled eggs, it seems to indicate the possibility that the same female lays several times over long periods. Future investigations are, of course, needed before more conclusive statements on this and other problems concerning reproduction can be made. 10. In its natural habitat, dahli is rather scarce and, moreover, hard to detect due to its secret habits. 11. They prefer rather shallow, quiet waters, where they mostly swim slowly close to the bottom with their long necks outstreched and the nose inclined downward in search of food, but are also able to swim quickly by means of their powerful, stronly webbed feet. 12. Equally well adapted to life on ground, they might be considered as virtually amphibious; active mainly from 5.30 - 7 a. m. and 5 - 7 p. m., they walk frequently over long distances; if persecuted, they run first very quickly and with their neck bent; cornered, they show a particular reaction: They stop and stretch out their hind legs until the anterior border of the shell becomes inclined and in contact with the ground; thus, the neck - never entirely covered by the shell - will be more protected; they remain in this position until the persecutor retires. 13. Apparently they undergo an Estivation; in captivity where water is plenty, they also lay hurried frequently in the soil or hidden in the shadow of underbrush under rotten leaves for several weeks, and are easily to confound with stones or rotten pieces of wood, due to the protective coloration of the grayish or olive brown upperside of their shells. 14. A strange habit was observed in specimens kept in the aquarium during the first months after being captured: Adults of both sexes, but more frequently the males, hit the glass or the border of the aquarium with their mandibles by means of very quick movements of the head; thus, the contact between the horny layer of the underside of mandible and the glass produces a series of klicking sounds; they did it only at night (8.00 - 10.00 p. m. approximately), rather frequently and each time for several seconds; this habit became lost after about four months in captivity.  Since movements and sounds produce vibrations in the water, this behavior may possibly be connected with some biological function, as e. g., to facilitate the meeting of the two sexes during mating season, or to announce the presence of an individual within a fixed territory, already occupied; the function could also be a combined one. 15. Specimens have been collected only from the type locality, Sincelejo (Bolivar), 200 meters high, but have been later reported by local inhabitants from different places within the same general region (see map). 16. Chelid turtles were formerly supposed to range only from Colombia, south of Cordillera Oriental, to northern Argentina, but now they are know to extend to north-western Colombia close to the shore of the Caribbean Sea. Since fossil shells of Chelus fimbriatus, together with others of a pelomedusid turtle, Podocemis spec., have been found at La Venta (Huila), a site belonging to Honda group of Late Miocene, situated north of Cordillera Oriental, it seems evident, that the range of the Chelidae extended farther north, before the last formation of the Eastern Andes during Pleistocene. Thus, there exists also the possibility that one or several members of this family had migrated as far as that region, actually still occupied by an isolated form, during Terciary.